A novel penning‐trap design for the high‐precision measurement of the 3He2 + nuclear magnetic moment - Schneider, Antonia; Mooser, Andreas; Rischka, Alexander; Blaum, Klaus; Ulmer, Stefan; Walz, Jochen (Annalen der Physik, 2019)
A new experiment is constructed aiming at the first direct high-precisionmeasurement of the helium-3 nuclear magnetic moment with a relativeprecision of parts-per-billion or better. Methods similar to those used inproton and antiproton magnetic moment measurements are applied. As thosetechniques rely on the challenging detection of single spin-flips, a novelPenning trap design optimized for nuclear spin-flip detection is developed.